Improved Antibacterial Activity of Water-Soluble Nanoformulated Kaempferol and Combretastatin Polyphenolic Compounds. (27th October 2021) - Santhosh Kumar, Y.; Kulanthaivel, Langeswaran; Hikku, G. S.; Saravanan, R.; Lakshmi, Thangavelu; Kirubhanand, C.; Karthikeyan, Murugesan; Vijayalakshmi, P.; Subbaraj, Gowtham Kumar
Abstract : Kaempferol and combretastatin are polyphenolic compounds derived from plant sources which are known for their antibacterial activity. However, owing to their large size and water insolubility, their antibacterial activity is limited. In this context, the present study focused on the nanoformulation of kaempferol (NF-k) and combretastatin (NF-c) and their influence on water solubility and antibacterial properties. The NF-k and NF-c were prepared using the solvent evaporation method and were thoroughly characterized for evaluating the morphology, molecular vibrations, size, etc. Based on the results, it is observed that the pristine forms of kaempferol and combretastatin drugs get nanoformulated and completely soluble in water. Using particle size analyzer, the particle sizes of NF-k and NF-c were estimated as 334 nm and 260 nm, respectively, which are very fine compared to pristine kaempferol and combretastatin (5193 nm and 1217 nm, respectively). The molecular vibrations that exist in NF-k and NF-c were confirmed by the Fourier transform infrared spectra, where the nanoformulated drug showed lower intensities than the pristine form of kaempferol and combretastatin. The drug release kinetics of the nanoformulated drugs were carried out using the dialysis membrane method and were compared with their pristine forms. Owing to the size effect, the NF-k and NF-c release up to 50% of the drug in a sustained manner till 50 h showing twofold higher concentration than the control where it released 25%. The antibacterial activity was assessed by measuring the optical density at 600 nm using UV-vis spectrophotometer and displayed significant activity against gram-positive Staphylococcus aureus strain. The mechanisms behind the antibacterial activity of NF-k and NF-c were discussed in detail. The activation of ATP-dependent efflux pump system and the blockage of porin channels could be the cause for the bactericidal activity. Our understanding of efflux pumps and their role in antibacterial activity is still in its early stages. No studies have been performed to date using nanoformulations of kaempferol and combretastatin to investigate their roles. This complicates the determination of the exact mechanisms acting against bacterial growth when using nanoformulation drugs. Our increasing knowledge of water-soluble nanoformulation drugs and their roles in reduced bacterial activity will pave the way to developing effective treatments in the future.